2016
DOI: 10.14257/ijseia.2016.10.1.16
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Mapping Review of Usability Evaluation Methods for Software Development Process

Abstract: Given that usability is one of the most important aspects of software quality, several methods have been developed in order to establish techniques capable of evaluating this attribute from early phases of the software development process. However, the choice of the most appropriate method for a particular scenario is still a difficult decision, due to the existence of a vast number of approaches that are described in the literature for this purpose. Therefore, a systematic mapping review was conducted in orde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
41
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 70 publications
(44 citation statements)
references
References 14 publications
1
41
0
2
Order By: Relevance
“…"Nowadays, usability is considered one of the most important aspects for the success of any technological product" (Paz & Pow-Sang, 2016, p.165). The top-5 methods for usability assessment comprising more than 70% of the applications are: questionnaires, user testing, heuristic evaluation, interview, and thinking aloud (Paz & Pow-Sang, 2016). The concept of user experiences denotes a broader approach than usability, including the (meta-)cognitive and emotional experiences of users when interacting with ICT within a specific context (Lallemand, Gronier & Koenig, 2015).…”
Section: Connection To Social Network and Communitiesmentioning
confidence: 99%
“…"Nowadays, usability is considered one of the most important aspects for the success of any technological product" (Paz & Pow-Sang, 2016, p.165). The top-5 methods for usability assessment comprising more than 70% of the applications are: questionnaires, user testing, heuristic evaluation, interview, and thinking aloud (Paz & Pow-Sang, 2016). The concept of user experiences denotes a broader approach than usability, including the (meta-)cognitive and emotional experiences of users when interacting with ICT within a specific context (Lallemand, Gronier & Koenig, 2015).…”
Section: Connection To Social Network and Communitiesmentioning
confidence: 99%
“…In a previous work [6], we conducted a systematic literature review to identify the most used methods to measure the degree of usability of software products. The heuristic evaluation was the third most relevant technique after the user testing and the questionnaire.…”
Section: A Formal Process To Evaluate the Usabilitymentioning
confidence: 99%
“…From the resulting papers of our systematic literature review, only those that illustrated in a way or another the use of the heuristic evaluation were considered. The list of papers is detailed in [6], but the new studies from 2016 that were incorporated to our analysis are [4], [5], [24], [29], [18], [14], [2] and [31]. The new evaluation process was structured in five phases according to the framework established by Hurtado et al [27] for usability inspection methods.…”
Section: A Formal Process To Evaluate the Usabilitymentioning
confidence: 99%
“…The author of the heuristic evaluation method only provides general recommendations to carry out this technique [10]. For this reason, we proposed a formal process based on a previous work [6], which involved the conduction of a systematic mapping review of the usability evaluation methods that were used during the last three years to develop software products. From these results, only those studies that reported the use of the heuristic evaluation method were analyzed.…”
Section: Usability Evaluation Protocolmentioning
confidence: 99%
“…In this work, we present the validation of a formal framework to conduct heuristic evaluations in the context of software products. This usability evaluation protocol was developed with basis on a previous systematic literature review [6].…”
Section: Introductionmentioning
confidence: 99%